Faktor-Faktor yang Memengaruhi Pergantian Kantor AKuntan Publik pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Mahantara, A.A. Gede Widya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2013)
Auditor switching that is conducted voluntary or outside the provision of KMK 423/KMK.06/2008 oftens raises questions among practitioners about the factor that causes it. Yet, its result keeps showing inconsistency. This study objective is to reinvestigate factors that influence going concern audit opinion. The factors used on this research are management change, firm growth, auditor reputation, financial distress, going concern opinion, company’s size, and decrease of ROA ratio. Hypotesis testing on this research was done by the logistic regression analysis. The hypotesis testing showed that management change have positive relationship to auditor switching. Variables of company size, auditor reputation, financial distress, and going concern opinion have negative relationship to going concern audit opinion. Variables of firm growth and decrease of ROA ratio have no relationship to going concern audit opinion.   Keywords: auditor switching, management change, firm growth, auditor reputation, financial distress.